Clinical strains of Lactobacillus reduce the filamentation of Candida albicans and protect Galleria mellonella against experimental candidiasis - Rossoni, Rodnei Dennis [UNESP]; dos Santos Velloso, Marisol [UNESP]; Figueiredo, Lívia Mara Alves [UNESP]; Martins, Carolina Pistille [UNESP]; Jorge, Antonio Olavo Cardoso [UNESP]; Junqueira, Juliana Campos [UNESP] (Springer Nature, 2018)
Candida albicans is the most common human fungal pathogen and can grow as yeast or filaments, depending on the environmental conditions. The filamentous form is of particular interest because it can play a direct role in adherence and pathogenicity. Therefore, the purpose of this study was to evaluate the effects of three clinical strains of Lactobacillus on C. albicans filamentation as well as their probiotic potential in pathogen-host interactions via an experimental candidiasis model study in Galleria mellonella. We used the reference strain Candida albicans ATCC 18804 and three clinical strains of Lactobacillus: L. rhamnosus strain 5.2, L. paracasei strain 20.3, and L. fermentum strain 20.4. First, the capacity of C. albicans to form hyphae was tested in vitro through association with the Lactobacillus strains. After that, we verified the ability of these strains to attenuate experimental candidiasis in a Galleria mellonella model through a survival curve assay. Regarding the filamentation assay, a significant reduction in hyphae formation of up to 57% was observed when C. albicans was incubated in the presence of the Lactobacillus strains, compared to a control group composed of only C. albicans. In addition, when the larvae were pretreated with Lactobacillus spp. prior to C. albicans infection, the survival rate of G. mellonela increased in all experimental groups. We concluded that Lactobacillus influences the growth and expression C. albicans virulence factors, which may interfere with the pathogenicity of these microorganisms.